ANALYSIS OF THE STUDENTS TENDENCY TO CONTINUE TO SENIOR HIGH SCHOOL IN IX GRADE STUDENTS AT SMP N 18 SURAKARTA IN 2019/2020 ACADEMIC YEAR - Ansari, Dimna Anjar; Kusumaningtyas, Lydia Ersta; Koesdyantho, AR (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
This research entitled Analysis of Students' Trends in Continuing Education in Senior High School in Class IX Students of SMP Negeri 18 Surakarta for the 2019/2020 Academic Year was conducted from August to September 2020 at SMP Negeri 18 Surakarta. This study aims to determine how to analyze the tendency of students to continue their education in high school in class IX students of SMP Negeri 18 Surakarta in the academic year 2019/2020 " The subjects of this study were class IX counselor, student affairs, parents class IX, and grade IX students. The object of this research is the analysis of the selection of further studies in high school by discussing it in a qualitative study. The data collection techniques used were interview, observation, and documentation methods. The validity of the data in this study was triangulation of sources and triangulation of techniques. In this study, data analysis using Miles and Huberman's model. Based on the data analysis, the conclusion is that 95% of students continue their education in high school, and 5% of students do not continue their education in high school. And as many as 30% of students continue their education in SMA on the grounds that they want to develop the academic field and want to continue their education at university, and 65% of students continue their education at SMK on the grounds that they want to work after graduating from SMK. In addition, the trend in continuing education in high school is strongly influenced by the guidance and counseling teachers who always provide motivation, information, and conduct individual counseling for students who find it difficult to determine education after graduating from junior high school, besides that the school and counselor collaborate with existing high schools in Soloraya to hold outreach to grade IX students. Thus, class IX students of SMP N 18 Surakarta in the 2019/2020 academic year tend to continue their education in high school after completing junior high school. Keywords: Continuing Education in Senior High School